Did God Care? : Providence, Dualism, and Will in Later Greek and Early Christian Philosophy - Burns, Dylan M., (Studies in Platonism, Neoplatonism, and the Platonic Tradition ;, 2020)
Is God involved? Why do bad things happen to good people? What is up to us? These questions were explored in Mediterranean antiquity with reference to 'providence' ( pronoia ). In Did God Care? Dylan Burns offers the first comprehensive survey of providence in ancient philosophy that brings together the most important Greek, Latin, Coptic, and Syriac sources, from Plato to Plotinus and the Gnostics. Burns demonstrates how the philosophical problems encompassed by providence transformed in the first centuries CE, yielding influential notions about divine care, evil, creation, omniscience, fate, and free will that remain with us today. These transformations were not independent developments of 'Pagan philosophy' and 'Christian theology,' but include fruits of mutually influential engagement between Hellenic and Christian philosophers.